THE IMPACT OF ANIMATION MEDIA ON THE CHARACTER OF CHILDREN IN TK STARLIGHT EDUCATION - Siti Rakiyah (Fakultas Ilmu Sosial UIN Sumatera Utara Medan, 2019)
This study reports research findings on the use of animated media in a application using in TK Starlight Education which meant to evaluate their effectiveness in supporting teaching and learning for young learners in TK Starlight Education. The researchers have developed a animated picture where designed from scratch using appropriate programs. The study was done in TK Starlight Education, and 15 students aged 4–5 years old participated in it. The research results provide evidence that the use of animated media significantly increases the young students’ knowledge and influenced their characteristic in social life, which are normally difficult to comprehend and often cause misconceptions to them and also they can used the new words.